Effect of Vegan Fecal Microbiota Transplantation on Carnitine‐ and Choline‐Derived Trimethylamine‐N‐Oxide Production and Vascular Inflammation in Patients With Metabolic Syndrome. Issue 7 (26th March 2018) - Smits, Loek P.; Kootte, Ruud S.; Levin, Evgeni; Prodan, Andrei; Fuentes, Susana; Zoetendal, Erwin G.; Wang, Zeneng; Levison, Bruce S.; Cleophas, Maartje C. P.; Kemper, E. Marleen; Dallinga‐Thie, Geesje M.; Groen, Albert K.; et al.
Abstract : Background: Intestinal microbiota have been found to be linked to cardiovascular disease via conversion of the dietary compounds choline and carnitine to the atherogenic metabolite TMAO (trimethylamine‐N‐oxide). Specifically, a vegan diet was associated with decreased plasma TMAO levels and nearly absent TMAO production on carnitine challenge. Methods and Results: We performed a double‐blind randomized controlled pilot study in which 20 male metabolic syndrome patients were randomized to single lean vegan‐donor or autologous fecal microbiota transplantation. At baseline and 2 weeks thereafter, we determined the ability to produce TMAO from d6 ‐choline and d3 ‐carnitine (eg, labeled and unlabeled TMAO in plasma and 24‐hour urine after oral ingestion of 250 mg of both isotope‐labeled precursor nutrients), and fecal samples were collected for analysis of microbiota composition. 18 F‐fluorodeoxyglucose positron emission tomography/computed tomography scans of the abdominal aorta, as well as ex vivo peripheral blood mononuclear cell cytokine production assays, were performed. At baseline, fecal microbiota composition differed significantly between vegans and metabolic syndrome patients. With vegan‐donor fecal microbiota transplantation, intestinal microbiota composition in metabolic syndrome patients, as monitored by global fecal microbial community structure, changed toward a vegan profile in some of the patients; however, no functional effects from vegan‐donor fecal microbiota transplantation were seen on TMAO production, abdominal aortic 18 F‐fluorodeoxyglucose uptake, or ex vivo cytokine production from peripheral blood mononuclear cells. Conclusions: Single lean vegan‐donor fecal microbiota transplantation in metabolic syndrome patients resulted in detectable changes in intestinal microbiota composition but failed to elicit changes in TMAO production capacity or parameters related to vascular inflammation. Clinical Trial Registration: URL:http://www.trialregister.nl . Unique identifier: NTR 4338.